O preconceito contra diversidade sexual e de gênero em escolas públicas de ensino médio brasileiras - Stucky, Juliana Ledur (2017)
This paper prepared as part of the researches conducted by the Research Group Prejudice, Vulnerability and Psychosocial Process of the Psychology School of the Pontifícia Universidade Católica do Rio Grande do Sul – PUCRS, had the goal to evaluate the grades of prejudice against sexual and gender diversity within 28 public schools of 12 cities located in 4 Brazilian states. In this paper, it were considered the manners which prejudice is expressed by teachers, staff and students, and the form that the prejudice is shown in relation to the social demographics variables researched in those three categories of subjects. The sample was based on 413 teachers, 97 employees and 1.829 high school students that answered a selfexplanatory questionnaire with social demographic data, duly reviewed by the Prejudice against Sexual and Gender Diversity scales. The questionnaire was composed by 16 items that inquired about prejudice against sexual and gender diversity, and the Bogardus scale of social distance adapted to investigated the relation among gays, lesbian, travesties and transexuals. Individuals that declared to be religious or followers of the evangelic religion in the three groups of study presented a higher rate of prejudice than the other variables. The participation in any training, class or course related to gender, sexuality or sexual diversity decreases the prejudice variable in the three groups of study. Individuals that affirmed to have homosexual (gays and lesbians) friends, relatives or acquaintances in the groups of teachers and students presented a lower level of prejudice compared to the ones that declared to not have relationship with people with such characteristics. To assist individuals that are part of Brazilian education institutions to think about multiple sexual and gender orientations is the first step to propose institutional, pedagogical and methodological changes in schools. Campaigns and political actions that foster the problem of the prejudice, their risks and damages for current and future generations is also fundamental for the search of a more equal society in relation to the individual rights and obligations.